Effect of HPV Infection on the Occurrence and Development of Laryngeal Cancer: A Review - Yang, Dongli (J Cancer, 2019)
Laryngeal cancer has the second highest incidence of head and neck malignant tumors worldwide. In recent years, studies have shown that human papillomavirus (HPV) infection may be a high-risk factor for laryngeal cancer and closely related to the development and prognosis of laryngeal cancer. The mechanism of the occurrence and development of laryngeal cancer caused by HPV infection needs investigation, as does a rapid and effective HPV detection method for effectively preventing the occurrence of laryngeal cancer and controlling its development. Many studies have explored the relation between HPV infection and laryngeal cancer. Here we review the research progress in investigating HPV infection in terms of DNA, mRNA and protein levels in the occurrence and development of laryngeal cancer and routine HPV detection methods.